Literature Analysis on the Role of Management Accounting in Strategic Decision Making - Rangkuti, Muhammad Ihsan (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2024)
Management accounting has a strategic role in supporting decision-making in various organizations. Through the collection, analysis, and interpretation of financial and non-financial data, management accounting enables companies to design effective, adaptive, and data-driven strategies. This article aims to analyze the current literature on the contribution of management accounting in strategic decision making, including performance measurement, cost analysis, strategic planning, internal control, and risk management. Using the literature review method, it is found that management accounting is not only an operational tool but also a crucial strategic partner. In addition, modern technologies such as data analytics and digital information systems further strengthen the role of management accounting in providing relevant and real-time information to support informed decision making. These findings suggest that the role of management accounting continues to evolve along with the need for organizations to maintain a competitive advantage amid complex business challenges